TDF Monotherapy Is Effective Regardless of Prior Nucleos(t)ide Analogue Treatment in Chronic Hepatitis B Patients in China. (12th April 2017) - Huang, Mingxing; Lin, Guoli; Shi, Hong; Wu, Yuankai; Jie, Yusheng; Zhu, Zhe; Chong, Yutian
Abstract : Background/Aims . Many patients had to transfer to tenofovir disoproxil fumarate (TDF) if there is other nucleos(t)ide analogue (NA) resistance. We aimed to investigate antiviral effects of TDF monotherapy between NA-naive and NA-experienced chronic hepatitis B (CHB) patients in China. Methods . A total of 102 NA-naive and NA-experienced CHB patients with TDF monotherapy (300 mg/day) were retrospectively analyzed for useful parameters up to 72 weeks. Results . There were 36 and 66 patients with matched HBV DNA baseline level in NA-naïve and NA-experienced group, respectively. There were no significant differences between NA-naïve and NA-experienced groups in HBV DNA levels (all P > 0.05 ) and HBV DNA undetectable rates (all P > 0.05 ) at all time points. At the end of follow-up, HBV DNA undetectable rates in NA-naïve and NA-experienced group were 96.2% (25/26) and 91.8% (45/49), respectively (P = 0.476 ). Baseline HBV DNA level was the only independent predictor for HBV DNA negative time (P = 0.018 ). In addition, 27.8% (5/18) and 11.4% (4/35) achieved HBeAg seroconversion at the end of the follow-up, respectively (P = 0.133 ). Conclusions . TDF monotherapy was effective regardless of prior NA experienced. Baseline HBV DNA was a key predictive factor for HBV DNA negative time in TDF monotherapy.